(untitled) (Advances in Knowledge Representation, 2023)
Foundation ontologies provide principles and theories aligned with a metamodel that can be used coherently in the construction of Knowledge Organization Systems (KOS) of specific domains. Conceptual domain models developed in accordance with a foundation ontology are called ontological models and should reflect in their scope and intention what was raised through the analysis of that domain, which reflects a point of view. Based on the recognition of the underlying epistemological and ontological perspectives, the points of view that are adopted to observe the domain are established, as well as principles and methods for its modeling and representation, in order to make its understanding and reuse clearer. How exactly the domain will be represented, the languages to be adopted, the formalisms and methodologies, all this depends to some extent on the objective of the ontology. In any case, the epistemological and ontological assumptions that influence the representation of the domain, as well as the principles adopted for its modeling, are often not clearly explained, leading to misunderstandings of the ontological commitment underlying these models. In this scenario, we aim to discuss aspects that are at the level of metamodels, to situate their importance, and how they impact conceptual models. As a result, a systematic, non-exhaustive framework of such aspects is presented, with examples of how they can affect existing KOS understanding.